Cobalt Phenanthroline–Indole Macrocycles as Highly Active Electrocatalysts for Oxygen Reduction. Issue 44 (3rd October 2014) - Quernheim, Martin; Liang, Haiwei; Su, Qi; Baumgarten, Martin; Koshino, Nobuyoshi; Higashimura, Hideyuki; Müllen, Klaus
Abstract The replacement of scarce and expensive platinum species poses a challenge in fuel‐cell development. The design and synthesis of a novel type of CoII–N4 macrocyclic complex, [CoN4], based on the phenanthroline–indole macrocyclic ligand (PIM) is reported. This unique ligand allows the formation of mono‐ and dinuclear complexes with defined active sites that facilitate the direct four‐electron reduction of oxygen. Electrochemical measurements revealed that the [CoN4]/C (20 wt %) catalysts have a high activity and long‐term stability for the oxygen‐reduction reaction (ORR) under alkaline conditions, similar to the Pt/C catalyst. These structurally well‐defined complexes represent a nonprecious alternative to platinum species for future fuel‐cell applications.